2022
DOI: 10.3390/antiox11040730
|View full text |Cite
|
Sign up to set email alerts
|

Lemon Balm and Corn Silk Mixture Alleviates Metabolic Disorders Caused by a High-Fat Diet

Abstract: We recently reported that varying combination ratios of lemon balm (Mellissa officinalis L.) and corn silk extracts (Stigma of Zea mays L. fruit) could reduce the obesity caused by a high-fat diet (HFD). The present study investigated the dose-dependent effect of a 1:1 (w:w) mixture of lemon balm and corn silk extracts (M-LB/CS) on HFD-mediated metabolic disorders and compared the effect with metformin. Oral administration of 50–200 mg/kg of M-LB/CS for 84 days significantly inhibited HFD-induced body weight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In addition, flavonoid content was quantified by measuring optical intensity at 415 nm wavelength after AsE was reacted with 0.2% aluminum nitrate and 20 mM potassium acetate for 40 min. Total flavonoids was expressed as mg of baicalein equivalents per gram of AsE, as described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, flavonoid content was quantified by measuring optical intensity at 415 nm wavelength after AsE was reacted with 0.2% aluminum nitrate and 20 mM potassium acetate for 40 min. Total flavonoids was expressed as mg of baicalein equivalents per gram of AsE, as described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Levels of lipid peroxidation and antioxidant defense system (e.g., reduced glutathione, superoxide dismutase activity and catalase activity) in lung homogenate were measured according to previously established method [ 21 ], and then normalized by protein concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in modern clinics, corn silk is applied to treat various diseases, such as nephritis, acute and chronic pneumonia, diabetes, hypertension, and edema [6]. In addition, many modern pharmacological activities, such as antihypertension activities [7], lowering blood lipids [8], anti-inflammatory activities [9], anti-urolithiasis activities [10], anti-oxidant activities [11], protecting the liver [12], and other effects [13] have been verified in previous studies.…”
Section: Introductionmentioning
confidence: 95%
“…Modern pharmacological studies showed that corn silk could be anti‐diabetic [1, 2], anti‐hyperuricemia [3], anti‐oxidant [4], anti‐cancer [5], anti‐obesity [6], anti‐inflammatory [7], lowering blood lipids [8], improving sleep disorders, etc. [9]. Besides, in clinical practice, corn silk was usually used as prescriptions combined with other TCMs, especially Xiaoke Pill [10, 11], and folk formula [12].…”
Section: Introductionmentioning
confidence: 99%